# math

solve using substitution
4x + 3y= -3
2x + y = -1

1. 👍
2. 👎
3. 👁
1. When we look at the second equation, we can transfer the term 2x to the other side of the equality. We get that:

2x+y = -1
<=> y = -1-2x

when we replace the y in the first equation by the value we just calculated, we get that:

4x + 3y= -3
<=> 4x + 3(-1-2x)=-3
<=> 4x - 3 -6x = -3
<=> -2x=0
<=> x=0

So, we find that x=0. When we replace this value for x in the equation we earlier found for y, we get that:

y=-1-(2*0)=-1

So, we find that x=0 and y=-1

1. 👍
2. 👎
2. thanxz

1. 👍
2. 👎

## Similar Questions

1. ### How do I do this.?(Math.)

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second

Solve using substitution. y = x – 2 x + y = 10 7x + 2y = - 8 8y = 4x Solve using elimination. 2x + 3y = 12 2x – y = 4 5x – 2y = - 19 2x + 3y = 0

What advantages does the method of substitution have over graphing for solving systems of equations? Choose the correct answer below. A. Graphing cannot be used to solve dependent or inconsistent systems due to the nature of the

4. ### math

What is the first step in solving the linear system {2x−3y=11 {−x+5y=−9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second equation

1. ### Algebra 2

Solve by Substitution x + 2y + z = 14 y = z + 1 x = -3z + 6

2. ### math

What is the first step in solving the linear system {2x − 3y = 11 {−x + 5y = −9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second

3. ### Intermediate algebra

5x - 2y = -62 -9x - 5y = 60 Solve by substitution

4. ### Algebra

Solve the system of equations using substitution. x + 4y = -5 3x - 8y = 45 When I tried to solve it, I got x=-17 and y=-3. When I plugged these into the first equation, it didn't work out at all. Could someone please show me the

1. ### math

solve using substitution y=4x-8 y=2x+10

2. ### Algebra

Solve using substitution 5x-2y= 0 and 3x=y =-1

3. ### math

solve by substitution 7x-2y=35 x-4y=5 2x+y=9 8x+4y=36

4. ### Math

Determine the point of intersection between a circle (x+2)^2 + (y-2)^2 =1 and the parabola y=-(x+2)^2 +3.can anyone please outline the steps to solve it I have tried solve by substitution but I get Stuck